Pengaruh Penambahan Isolat Cair Terhadap Karakteristik Kedelai Terfermentasi - Susi Kartika, Ni Made; Suparthana, I Putu; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i03.p02, 2021)
This research aims to determine the effect of adding different amounts of liquid isolate with fermentation time of 24 hours and to obtain the correct addition of liquid isolate to produce fermented soybeans with the best characteristics. Completely Randomized Design (CRD) was used in this research with the addition of liquid isolate treatment consisting of 5 levels namely 1%, 2%, 3%, 4%, 5%. Each treatment was repeated 3 times, resultd 15 experimental units. The data were analyzed using the Analysis of Variance (ANOVA) and if the treatment affected the observed variable, it was followed by the Duncan’s Multiple Range Test. The results showed that the addition of a liquid isolate had a very significant effect on moisture, ash, protein, fat, carbohydrate, total bacteria content, hedonic test color, aroma, texture and overall acceptance of fermented soybeans. The best characteristics were obtained from the addition of 1% liquid isolate with the criteria : 18,13% moisture content 2,39% ash content, 11,81% carbohydrate content, total bacteria 9,01log cfu/g, with like color, aroma, texture and overall acceptance.